Have you Heard What They Are Doing to Women? Media Portrayal of Female Celebrities in Nigerian Press - Aondover Eric Msughter; Martha Msoo Hile; Fatima Salihu Bappa (Budapest International Research and Critics University, 2022)
The globalized culture of celebrity is argued to have profound effect on knowledge, power and representation. Celebrity culture as a popular culture promoted through the media influence certain categories of group. The study used quantitative content analysis to examine the portrayal of female celebrities in the Daily Trust and The Nation newspapers. The study used purposive sampling technique to select the newspaper, and stratified sampling by days of the week to select the editions. The study used framing theory to examine the coverage and portrayal of female celebrities in the two selected newspapers. The findings suggest that the media should be cognizant of the harmful and erroneous impressions that can result from portraying female celebrities in terms of their attributes rather than their professional accomplishment. The study concludes that issues concerning Nigerian female celebrity are seriously lacking both inequality and quantity. Despite the active involvement of females in the entertainment industry, they are still being fitted and portrayed in negatively stereotypic ways. The relationship between the media and the society is a symbiotic one - the media feeds ‘from’ and ‘into’ the society hence, whatever the media portrays as ‘normal’ and prominent is what the society sees as so. Therefore, there is an urgent need to improve the representation of women in the media by increasing the quality and quantity of news stories about women.